العوامل المؤثرة في سياسة توزيع الأرباح النقدية للشركات المدرجة في سوق دمشق للأوراق المالية - نادر نهاد; حيدر وئام (Latakia University Journal - Economic and Legal Sciences Series, 2016)
This study examined the factors affecting cash dividends policy of listed companies in Damascus Securities Exchange(DSE) during year 2009 to 2013.Using the TOBIT regression analysis, the study did not include year 2014 because the financial results of the meetings of their general assemblies noanunciarso far. The study found that: Each of profitability and liquidity are noteffectat5% significant level, where thevalueexceededthe0.05 significance. The existence of investment opportunities negatively affects on the dividend decision at the level of 5% significant as an increase in investment limit distributions because of the need to finance. Indebtedness adversely affect the dividend, The higher debt ratio decreased dividends. Company size does not affect significantly the dividend at 5% significant level. Finally sector Type affects the dividend policy, The companies in the insurance industry, agriculture and services sectors more breakdown of the profits more companies in the other sectors. اختبرت هذه البحث العوامل المؤثرة على سياسة توزيع الأرباح النقدية للشركات المدرجة في سوق دمشق للأوراق المالية.استخدمت البحث نموذج انحدار TOBIT لدراسة العلاقة بين المتغيرات, وغطت حالات توزيع الأرباح بين عامي 2009-2013 ولم تشمل البحث عام 2014 لعدم صدور النتائج المالية وانعقاد اجتماعات جمعياتها العمومية حتى تاريخ إعداد هذا البحث. توصلت البحث إلى أن: كل من الربحية والسيولة ليستا ذات أثر معنوي عند مستوى ثقة 5% إذ إن قيمة الدلالة تجاوزت 0.05. يؤثر وجود فرص استثمارية سلباً على قرار توزيع الأرباح عند مستوى ثقة5% و إن زيادة الاستثمارات تحد من التوزيعات بسبب الحاجة لتمويل. يؤثر حجم المديونية سلباً على توزيعات الأرباح فكلما زادت نسبة المديونية قلت توزيعات الأرباح. حجم الشركة لايؤثر معنوياً على توزيعات الأرباح عند مستوى ثقة 5%. وأخيراً يؤثر نوع القطاع على سياسة التوزيعات, فشركات كل من قطاع التأمين والزراعة والخدمات أكثر توزيعاً للأرباح من الشركات في القطاعات الأخرى.